The effect of chia (Salvia hispanic L.) flour as a substitute for fat in gluten-free bread. Issue 4 (15th November 2018) - Huerta, Katira da Mota; Boeira, Caroline Pagnossim; Soquetta, Marcela Bromberger; Alves, Jamila dos Santos; Kubota, Ernesto Hashime; da Rosa, Claudia Severo
Abstract : Purpose: The preparation of gluten-free bread is a challenge because the gluten in wheat is the main ingredient responsible for the retention of the gases which cause the bread to rise. This paper aims to develop breads without gluten and fat, and to evaluate the effect of the use of chia ( Salvia hispanic L. ) flour on the physical, nutritional and sensory properties of the breads that were developed. Design/methodology/approach: Three formulations were developed with different proportions of chia flour (2.5, 5 and 7.5%), fat-free. Physiochemical, sensorial analyses were performed out in three repetitions ( p -value = 0.05). Findings: In the nutritional assessment, the results demonstrated that 7.5% chia showed higher levels of protein (15.1%), lipid (3.43%), total fiber (7.04%) and lower levels of carbohydrates (22.49%), with significant nutrient enrichment ( p -value = 0.05). The specific volume and the elevation of the dough decreased with the addition of chia flour. In the sensorial analysis, the treatments with chia flour showed no significant difference regarding flavor and texture when compared to the standard. The addition of chia improved the nutritional and sensory properties ( p -value = 0.05). Originality/value: The chia flour improved the nutritional characteristics of the breads, in the reduction of carbohydrate content and the increase in the content of protein, minerals and fiber. It presented good acceptability and good nutritional characteristics, providing a healthy and differentiated variation in this segment.